Tudo Ressoa: vozes e dramaturgias da memória autoficcional no teatro performativo - Baldo, Lysiane Cassia (2021)
According to the development of several theoretical and practical propositions in some studies that lead the actor/performer to the focus of discussion of creative processes, profiles of contemporary theater are applied by performativity, in which the limits of theatricality are explored and, in some cases, even put in check. Dramatic theater can no longer embrace the needs of scenic experiments, which wide up in their forms of expression and point toward new horizons. The new possibilities for the scene bring structural changes to the field of dramaturgical creation and an expansion of dramaturgy concept is crucial. Thus, this study regarding “Me myself” is evidenced along the creating processes of a performative theater, which touches the boundaries between real and fictional and whose memory is at the core of the creative procedures of the actor/performer. According to this path, the central theme of this research comes out: dramaturgy of self-fictional memory in performative theater. Based on these assumptions and, taking as its corpus some artistic works of relevance in this theme and references in the performing arts, the objective is to understand how dramaturgy of memory is built along the creating processes of Kintsugi shows: 100 memories (2019) of Lume Teatro and Stabat Mater (2019) by actress Janaina Leite and to investigate it also from the perspective of a practical experience of scenic and dramaturgical creation. Therefore, the following questions were raised: from what perspectives has memory been set up in these shows/works? How can limits between “real” and fictional be defined in these scenic works? The methodology applied was based on the compared literature in text/ scene/ performativity analyses for composition processes. The theoretical scope pervades the core axes: dramaturgy, memory, self-fiction and performativity, delimiting itself mainly on the following authors: Hans-Thies Lehmann (1944- ), Renato Cohen (1956-2003), Josette Féral (1949-), Henri-Bergson (1859- 1941), among others. The author's self-fictional scenic investigation process is reported in the last chapter as a deployment, an understanding that pervades her body-memory in a ‘memory dramaturgy’ construction that, when is born in the scene, reaches the text.